2020
DOI: 10.1038/s41390-020-0971-x
|View full text |Cite
|
Sign up to set email alerts
|

Changes in pulmonary oxygen content are detectable with laser absorption spectroscopy: proof of concept in newborn piglets

Abstract: BACKGROUND: Using an optical method based on tunable diode laser absorption spectroscopy, we previously assessed oxygen (O 2) and water vapor (H 2 O) content in a tissue phantom of the preterm infant lung. Here we applied this method on newborn piglets with induced lung complications. METHODS: Five mechanically ventilated piglets were subjected to stepwise increased and decreased fraction of inspired oxygen (FiO 2), to atelectasis using a balloon catheter in the right bronchus, and to pneumothorax by injecting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 25 publications
(31 reference statements)
1
12
0
Order By: Relevance
“…We note that lung oxygen measurements in adults using GASMAS has so far not been possible, due to longer path‐lengths/larger geometries, leading to extremely low light intensities reaching the detector, as compared to the successful measurements on neonatal lungs, previously reported by our research group [31, 32]. The possibility to promptly identify severe lung complications, for example, pneumothorax (collapsed lung due to air leakage in the space between the lung and the chest wall) or atelectasis (collapsed lung due to deflated alveoli), using the GASMAS technique in an animal model has also been demonstrated [35]. The need for a noninvasive, harmless, continuous lung surveillance technique for preterm/ill infants is clear, and there is, of course, a corresponding need for adults, where many patients suffer from severe respiratory disorders, for example, pneumonia, chronic obstructive pulmonary disease, lung fibrosis and more recently the SARS‐CoV‐2 viral infection.…”
Section: Discussionmentioning
confidence: 75%
See 2 more Smart Citations
“…We note that lung oxygen measurements in adults using GASMAS has so far not been possible, due to longer path‐lengths/larger geometries, leading to extremely low light intensities reaching the detector, as compared to the successful measurements on neonatal lungs, previously reported by our research group [31, 32]. The possibility to promptly identify severe lung complications, for example, pneumothorax (collapsed lung due to air leakage in the space between the lung and the chest wall) or atelectasis (collapsed lung due to deflated alveoli), using the GASMAS technique in an animal model has also been demonstrated [35]. The need for a noninvasive, harmless, continuous lung surveillance technique for preterm/ill infants is clear, and there is, of course, a corresponding need for adults, where many patients suffer from severe respiratory disorders, for example, pneumonia, chronic obstructive pulmonary disease, lung fibrosis and more recently the SARS‐CoV‐2 viral infection.…”
Section: Discussionmentioning
confidence: 75%
“…In scaling up lung monitoring from newborn to larger children or adults, internal light administration is clearly advantageous over light injection from the surface of the chest [33–35]. Internal fiber‐optical light administration would not present any major complication, since the patients mostly in need would anyway be intubated with an endotracheal tube, connected to a ventilator.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A larger study on 29 newborn infants demonstrated transcutaneous detection of oxygen in the lungs using GASMAS [20]. This approach was further validated also on a piglet animal model [21]. Yet, to the best of our knowledge, so far no non-invasive optical approach has been applied in vivo on the lungs in adults.…”
Section: Introductionmentioning
confidence: 89%
“…Trace gas detection has numerous significant applications in various fields, such as biomedical analyses [1,2], combustion diagnosis [3][4][5], atmospheric environmental monitoring [6][7][8][9], as well as petroleum exploration [10,11]. Gas sensing technology based on laser absorption spectroscopy (LAS) has a number of advantages, including high sensitivity, rapid response time, high selectivity, et al [12].…”
Section: Introductionmentioning
confidence: 99%